Adsorption of Malic Acid on Activated Charcoal - Inci, Ismail (Asian Journal of Chemistry, 2016)
Attempts were made to adsorb malic acid from aqueous solutions by activated charcoal. Adsorption experiments were carried out in the system of aqueous malic acid solutions in four different concentrations [3, 5, 10 and 15 (w/w)] and in seven different amounts of activated charcoal (0.005, 0.010, 0.015, 0.020, 0.025, 0.030 and 0.040 g) as adsorbent. Adsorption experiments were carried out at 298 K. The adsorption of malic acid was found to be appreciable in activated charcoal. The percentage removal of malic acid was 94.14% by activated charcoal. The equilibrium data fit well within Langmuir and Freundlich isotherms.